2021
DOI: 10.1021/acs.jafc.1c00130
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Metabolomics and Full-Length RNA-Seq Reveal Effects of Acylated and Nonacylated Anthocyanins on Hepatic Metabolites and Gene Expression in Zucker Diabetic Fatty Rats

Abstract: Anthocyanins have been reported to possess antidiabetic effects. Recent studies indicate acylated anthocyanins have better stability and antioxidative activity compared to their nonacylated counterparts. This study compared the effects of nonacylated and acylated anthocyanins on hepatic gene expression and metabolic profile in diabetic rats, using full-length transcriptomics and 1 H NMR metabolomics. Zucker diabetic fatty (ZDF) rats were fed with nonacylated anthocyanin extract from bilb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…A high level of urinary glucose in ZDF rats indicates a high level of plasma glucose and/or renal dysfunction. Our previous studies have shown acylated anthocyanins from purple potato have more potential to decrease plasma and hepatic glucose levels, , and in this study, only a high dose of acylated anthocyanin extracts (AAPP) decreased urinary glucose. Urinary lactate level was higher in the diabetic group than in the lean Zucker rats.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A high level of urinary glucose in ZDF rats indicates a high level of plasma glucose and/or renal dysfunction. Our previous studies have shown acylated anthocyanins from purple potato have more potential to decrease plasma and hepatic glucose levels, , and in this study, only a high dose of acylated anthocyanin extracts (AAPP) decreased urinary glucose. Urinary lactate level was higher in the diabetic group than in the lean Zucker rats.…”
Section: Discussionmentioning
confidence: 55%
“…Correlation analysis of urinary metabolites to plasma metabolites and clinical traits was conducted based on a debiased sparse partial analysis in Cytoscape (Version:3.2.1; ) ( r > 0.4 or r < −0.4; p < 0.05). In our previous study, we measured the plasma, hepatic, and fecal metabolites, fecal microbiota, as well as clinical traits, which were used for correlation analysis with the urine metabolites in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…T2D is a serious disease characterized by disturbed lipid and glucose metabolism as well as inflammatory response disorders [ 17 ]. Therefore, the regulation of lipid and glucose metabolism and inflammation is one of the strategies for the treatment and management of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics and transcriptomics have been demonstrated to be powerful approaches to reveal the variations in the complicated regulatory networks of metabolic pathways . Barley sprouts have a protective influence on the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics and transcriptomics have been demonstrated to be powerful approaches to reveal the variations in the complicated regulatory networks of metabolic pathways. 27 Barley sprouts have a protective influence on the liver. Metabolomic analysis identified metabolite alterations in the fatty acid synthesis pathway of habitual alcohol drinkers upon the consumption of barley sprouts, which was similar to our results.…”
Section: ■ Discussionmentioning
confidence: 99%